Artificial Intelligence and Quantum Computing: Early Innovations - Ogunji, S. T.; Sánchez Adame, M.; Montiel, O.; Martínez Quiroz, Marisela (SPRINGER link, 2025)
In this work, we present a detailed analysis of the BB84 Quantum Key Distribution (QKD) protocol implementation using Qiskit’s quantum circuit simulation framework. Our study examines protocol performance across five commonly studied quantum noise models: depolarizing, amplitude damping, phase damping, generalized amplitude damping, and Pauli channels. The implementation incorporates Cascade error correction and Toeplitz matrix-based privacy amplification, evaluated through systematic simulations with key lengths ranging from 100 to 5000 qubits and error rates varying between 0.01 and 0.2. Using Qiskit’s matrix_product_state simulator, we analyze the relationships between measured error rates, achieved key rates, and theoretical Holevo bounds under various noise conditions. These results highlight distinct performance patterns across noise models, with optimal key rates varying significantly based on the noise environment. These findings offer valuable insights into the practical limitations and capabilities of BB84 QKD in noisy quantum channels, providing guidelines for implementing robust error correction and privacy amplification strategies
Performance Dynamics of BB84 QKD Protocol in Noisy Quantum Channels: A Simulation Study
Keywords: Depolarizing; Amplitude damping; Phase damping; Generalized amplitude damping; Pauli channels; Campus Tijuana